2021
DOI: 10.1101/2020.12.29.20248976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laboratory Biomarkers of COVID-19 Disease Severity and Outcome: Findings from a Developing Country

Abstract: AimTo identify laboratory biomarkers that predict disease severity and outcome among COVID-19 patients admitted to the Millennium COVID-19 Care Center in Ethiopia.MethodsA retrospective cohort study was conducted among 429 RT-PCR confirmed COVID- 19 patients who were on follow up from July to October 2020 and with complete clinical and laboratory data. Data was described using frequency tables. Robust Poisson regression model was used to identify predictors of COVID-19 disease severity where adjusted relative … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…20 Leulseged et al study also reported cough (69.2%), dyspnea (34.5%), and fever (26.1%) in COVID-19 cases. 2 The study showed that presenting features such as a high respiratory rate due to dyspnea would increase the OR for mortality.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 Leulseged et al study also reported cough (69.2%), dyspnea (34.5%), and fever (26.1%) in COVID-19 cases. 2 The study showed that presenting features such as a high respiratory rate due to dyspnea would increase the OR for mortality.…”
Section: Discussionmentioning
confidence: 98%
“…1 The severity was significantly associated with elderly individuals and those with underlying comorbid conditions like diabetes mellitus (DM), hypertension, chronic kidney disease, underlying cardiac diseases, sickle cell disease, asthma, chronic obstructive pulmonary disease, and many more. 2 3 Sudden onset of acute respiratory distress syndrome due to coronavirus disease 2019 (COVID-19) warrants early assessment of severity and intervention to reduce the mortality. Clinical judgment regarding the disease progression is complex and purely relies on blood test reports.…”
Section: Introductionmentioning
confidence: 99%